Large-Game Hunting in the American West: A Comment on Fisher's (2015) Reassessment of the Ascendance of Hunting Debate. Issue 4 (October 2016) - Hildebrandt, William R.; McGuire, Kelly R.
Abstract : Fisher's (2015) reanalysis of data presented by Hildebrandt and McGuire (2002) fails to include the original finding that the Middle Archaic was the trans-Holocene high-point of large-game hunting in southeastern California, nor does his reliance on climatic change contribute anything new to the ascendance of hunting debate.